2009
DOI: 10.1371/journal.pone.0005468
|View full text |Cite
|
Sign up to set email alerts
|

CHOP Mediates Endoplasmic Reticulum Stress-Induced Apoptosis in Gimap5-Deficient T Cells

Abstract: Gimap5 (GTPase of the immunity-associated protein 5) has been linked to the regulation of T cell survival, and polymorphisms in the human GIMAP5 gene associate with autoimmune disorders. The BioBreeding diabetes-prone (BBDP) rat has a mutation in the Gimap5 gene that leads to spontaneous apoptosis of peripheral T cells by an unknown mechanism. Because Gimap5 localizes to the endoplasmic reticulum (ER), we hypothesized that absence of functional Gimap5 protein initiates T cell death through disruptions in ER ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 54 publications
2
33
0
Order By: Relevance
“…Impairment of ER function and activation of ER stress responses have been implicated in lipoapoptosis pathways in various cell types including liver cells (2,7,22,24,26,38,39,43). With regard to lipids, saturated FFA, but not unsaturated FFA, result in an ER stress response with the induction of the transcription factor CHOP in liver cells (2,39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Impairment of ER function and activation of ER stress responses have been implicated in lipoapoptosis pathways in various cell types including liver cells (2,7,22,24,26,38,39,43). With regard to lipids, saturated FFA, but not unsaturated FFA, result in an ER stress response with the induction of the transcription factor CHOP in liver cells (2,39).…”
Section: Discussionmentioning
confidence: 99%
“…CHOP has been implicated as a key mediator of ER stress-induced cell death in various cell types including murine fibroblasts (43), lymphocytes (26) and pancreatic ␤-cells (8,22,24). Indeed, CHOP knockdown confers protection against lipoapoptosis in pancreatic ␤-cells (8) and reduces hepatocyte apoptosis in alcoholinduced liver injury (13).…”
mentioning
confidence: 99%
“…CHOP (CCAAT/enhancer-binding protein homologous protein, also known as growth arrest and DnA damage-inducible protein) is a transcription factor which is up-regulated and plays a critical role in ERS-mediated apoptosis (17,38). The fact that overexpression of CHOP results in growth arrest and apoptosis has been demonstrated in a rat model (39) and in Hl-60 cells (40).…”
Section: Discussionmentioning
confidence: 99%
“…However, prolonged activation of ER stress ultimately initiates the apoptotic pathway. C/EBP homologous protein (CHOP) is an important protein in ER stress-mediated apoptosis (15). A number of previous studies have demonstrated that the ER is the major cell death organelle in cadmium-induced mesangial cell apoptosis (16), glomerular and tubular damage in kidney disease and renal injury (17,18).…”
Section: Introductionmentioning
confidence: 99%